Reversal of biological age in multiple rat organs by young porcine plasma fraction - Steve Horvath; Kavita Singh; Ken Raj; Shraddha I. Khairnar; Akshay Sanghavi; Agnivesh Shrivastava; Joseph A. Zoller; Caesar Z. Li; Claudia B. Herenu; Martina Canatelli-Mallat; Marianne Lehmann; Siniša Habazin; et al. (GeroScience, 2023)
Young blood plasma is known to confer beneficial effects on various organs in mice and rats. However, it was not known whether plasma from young adult pigs rejuvenates old rat tissues at the epigenetic level; whether it alters the epigenetic clock, which is a highly accurate molecular biomarker of aging. To address this question, we developed and validated six different epigenetic clocks for rat tissues that are based on DNA methylation values derived from n = 613 tissue samples. As indicated by their respective names, the rat pan-tissue clock can be applied to DNA methylation profiles from all rat tissues, while the rat brain, liver, and blood clocks apply to the corresponding tissue types. We also developed two epigenetic clocks that apply to both human and rat tissues by adding n = 1366 human tissue samples to the training data. We employed these six rat clocks to investigate the rejuvenation effects of a porcine plasma fraction treatment in different rat tissues. The treatment more than halved the epigenetic ages of blood, heart, and liver tissue. A less pronounced, but statistically significant, rejuvenation effect could be observed in the hypothalamus. The treatment was accompanied by progressive improvement in the function of these organs as ascertained through numerous biochemical/physiological biomarkers, behavioral responses encompassing cognitive functions. An immunoglobulin G (IgG) N-glycosylation pattern shift from pro- to anti-inflammatory also indicated reversal of glycan aging. Overall, this study demonstrates that a young porcine plasma-derived treatment markedly reverses aging in rats according to epigenetic clocks, IgG glycans, and other biomarkers of aging.

Seaweed ethnobotany of eastern Sorsogon, Philippines - Richard V. Dumilag; Teresa Haide R. Belgica; Lynn C. Mendoza; Janet M. Hibay; Abel E. Arevalo; Mark Ariel D. Malto; Elden G. Orgela; Mabille R. Longavela; Laurence Elmer H. Corral; Ruby D. Olipany; Caesar Franz C. Ruiz; Cynthia B. Mintu; et al. (Algae, 2022)
Knowledge on the seaweeds of eastern Sorsogon in the Philippines is uneven. Not only is eastern Sorsogon among the areas of high seaweed diversity but locals there have interacted with seaweeds for ages. Despite seaweeds’ assumed importance to Sorsoganon, ethnobotanical records are missing. In this study, we documented the traditional knowledge on seaweed use and determined the rate of knowledge transmission among the locals of eastern Sorsogon. Vernacular names and modes of preparation were given of the 12 identified species bearing culinary and medicinal importance. Ten species were eaten while three were used therapeutically. Based on ethnobotanical indices, Caulerpa chemnitzia ecad turbinata and Gelidiella acerosa were the most important seaweeds. The least cited was Caulerpa racemosa. Our study demonstrated that most of the seaweed resources in eastern Sorsogon remain largely untapped, as the identified ethnotaxa were only about 5% of the total seaweed species diversity reported for the area. The seaweed knowledge in eastern Sorsogon appeared to be homogenous across age groups with primary sources of knowledge biased towards female relatives (mothers and grandmothers) and to children as inheritors. Cessation of seaweed knowledge may come at a potential cost, as a significant fraction of the population did not transmit their knowledge to others. Our study furthered the interest in providing sophisticated resource management recommendations that consider the relationships of traditional and scientific knowledge of seaweed selection and use in eastern Sorsogon and beyond.

Scaling issues of neutral theory reveal violations of ecological equivalence for dominant Amazonian tree species - Edwin Pos; Juan Ernesto Guevara; Jean‐François Molino; Daniel Sabatier; Olaf S. Bánki; Nigel C.A. Pitman; Hugo F. Mogollón; Roosevelt García‐Villacorta; David Neill; Oliver L. Phillips; Carlos Cerón; Marcos Ríos Paredes; et al. (Ecology Letters, 2019)
Neutral models are often used as null models, testing the relative importance of niche versus neutral processes in shaping diversity. Most versions, however, focus only on regional scale predictions and neglect local level contributions. Recently, a new formulation of spatial neutral theory was published showing an incompatibility between regional and local scale fits where especially the number of rare species was dramatically under‐predicted. Using a forward in time semi‐spatially explicit neutral model and a unique large‐scale Amazonian tree inventory data set, we show that neutral theory not only underestimates the number of rare species but also fails in predicting the excessive dominance of species on both regional and local levels. We show that although there are clear relationships between species composition, spatial and environmental distances, there is also a clear differentiation between species able to attain dominance with and without restriction to specific habitats. We conclude therefore that the apparent dominance of these species is real, and that their excessive abundance can be attributed to fitness differences in different ways, a clear violation of the ecological equivalence assumption of neutral theory.

What are the implications of sea-level rise for a 1.5, 2 and 3 °C rise in global mean temperatures in the Ganges-Brahmaputra-Meghna and other vulnerable deltas? - Sally Brown; Robert J. Nicholls; Attila N. Lázár; Duncan D. Hornby; Chris Hill; Sugata Hazra; Kwasi Appeaning Addo; Anisul Haque; John Caesar; Emma L. Tompkins (Regional Environmental Change, 2018)

North Atlantic observations sharpen meridional overturning projections - R. Olson; S.-I. An; Y. Fan; J. P. Evans; L. Caesar (Climate Dynamics, 2018)

West Africa climate extremes and climate change indices - A. A. Barry; J. Caesar; A. M. G. Klein Tank; E. Aguilar; Carol McSweeney; Ahmed M. Cyrille; M. P. Nikiema; K. B. Narcisse; F. Sima; G. Stafford; L. M. Touray; J. A. Ayilari‐Naa; et al. (International Journal of Climatology, 2018)
Observational analyses of changing climate extremes over the West Africa region have been limited by the availability of long and high‐quality datasets. To help address this gap, a climate extremes indices workshop was held in the Gambia in December 2011 with participants from 14 West African countries. The resulting analysis utilized 15 annual indices derived from observed daily temperatures and 10 annual indices derived from observed daily precipitation. The analysis was conducted for 166 meteorological stations in 13 countries for 2 periods: 1960–2010 and 1981–2010. The analyses of trends in the annual mean temperature indices have identified statistically significant increases of 0.16 °C/decade and 0.28 °C/decade for mean annual maximum and mean annual minimum temperatures, respectively, averaged over all available land stations in the region during the last 50 years. The seasonal‐temperature‐related indices show significant patterns of warming in all seasons. The annual mean of daily minimum temperature has increased more than the annual mean of daily maximum temperature leading to a decreasing trend in the diurnal temperature range. Warm days and warm nights have become more frequent, and cold days and cold nights have become less frequent. The analyses of precipitation‐based indices indicate spatially non‐coherent changes throughout the study area with few statistically significant trends over the longer period. Exceptions to this are the simple daily intensity index and maximum 5‐day precipitation, which show significant increasing regional trends over both the shorter and longer periods. Additionally, over the recent period (1981–2010) most of the precipitation related indices show significant trends towards wetter conditions. However, this period of increased rainfall follows a decade of significantly drier conditions in the region – it is not clear whether the recent upward trends reflect the ‘recovery’ from this long drought period or represents a long‐term response to warming.

Dryland soil nitrogen cycling influenced by tillage, crop rotation, and cultural practice - Upendra M. Sainju; Andrew W. Lenssen; Thecan Caesar-TonThat; Jalal D. Jabro; Robert T. Lartey; Robert G. Evans; Brett L. Allen (Nutrient Cycling in Agroecosystems, 2012)

Changes in temperature and precipitation extremes over the Indo‐Pacific region from 1971 to 2005 - J. Caesar; L. V. Alexander; B. Trewin; K. Tse‐ring; L. Sorany; V. Vuniyayawa; N. Keosavang; A. Shimana; M. M. Htay; J. Karmacharya; D. A. Jayasinghearachchi; J. Sakkamart; et al. (International Journal of Climatology, 2011)
Up‐to‐date regional and local assessments of changing climate extremes are important to allow countries to make informed decisions on mitigation and adaptation strategies, and to put these changes into a global context. A workshop for countries from the Indo‐Pacific region has brought together daily observations from 13 countries for an analysis of climate extremes between 1971 and 2005. This paper makes use of the workshop outcomes and post‐workshop analyses to build on previous work in Southeast Asia to update the assessment of changing climate extremes using newly available station data. We utilise a consistent and widely tested methodology to allow a direct comparison of the results with those from other parts of the world. The relationship of inter‐annual variability in the climate extremes indices with sea surface temperature (SST) patterns has been investigated with a focus on the influence of the El Niño‐Southern Oscillation phenomenon. The results support findings from elsewhere around the globe that warm extremes, particularly at night, are increasing and cold extremes are decreasing. Trends in precipitation extremes are less spatially consistent across the region. © Royal Meteorological Society and Crown Copyright 2010.

Long-term tillage and cropping effects on microbiological properties associated with aggregation in a semi-arid soil - TheCan Caesar-TonThat; Upendra M. Sainju; Sara F. Wright; Weilin L. Shelver; Robert L. Kolberg; Mark West (Biology and Fertility of Soils, 2011)

Dryland residue and soil organic matter as influenced by tillage, crop rotation, and cultural practice - Upendra M. Sainju; Andrew W. Lenssen; Thecan Caesar-TonThat; Jalal D. Jabro; Robert T. Lartey; Robert G. Evans; Brett L. Allen (Plant and Soil, 2011)

Soil aggregate stabilization by a saprophytic lignin-decomposing basidiomycete fungus I. Microbiological aspects - T.-C. Caesar-TonThat; V. L. Cochran (Biology and Fertility of Soils, 2000)